HUBUNGAN ORIENTASI PENGURUS LAZ TERHADAP NILAI SOSIAL EKONOMI: PEMANFAATAN ZAKAT DENGAN KEBIJAKAN PIMPINAN - Dudi Abdul Hadi; Yane Devi Anna (Jurnal Ekonomi & Keuangan Islam, 2011)
This research is intended to know about accountability in the relation between amil of LAZ, that is the chief of zakah distribution and the leader of LAZ. The research is conÂducted at five registered lembaga amil zakat (LAZ) in Bandung. The research is descriptive explorative survey and uses quantitave approach. The data analysis uses the Pearson Product Moment correlation coefficient. All hypothesis testing of the statements result in nonzero value of the Pearson Product Moment correlation coefficient. It can be concluded primarily that orientation of LAZ amil toward socioeconomic value of zakah utilization and leader policy are highly correlated by the amount of 0,9092.